HYGIENIC CHARACTERISTICS OF THE SPECIFIC CONDITIONS IN MODERN MILITARY PILOTS’ PROFESSIONAL ACTIVITIES - Kravchuk, V.V.; Shchepankov S.М.; Shepitko, K.V.; Pashkovsky, S.M. (World of Medicine and Biology, 2020)
On the basis of the systems analysis the paper highlights the complex as such and suggests the comparative characteristics of the organizational, climatic, psychogenic, socially and politically stipulated factors, and determines their importance for the particular categories of military pilots of the Peacekeeping Forces and Joint Forces Operation. According to the data of the meteorological surveillance the assessment of the climatic conditions in the area of Robertsfield (Liberia) aerodrome are made and their distinctions as compared to the places of permanent deployment on the territory of Ukraine are presented. It has been established that it is not the persistently high indices of the air temperature which are within the boundaries of the comfort temperature sensing, but the absence of traditional variations during the day, high indices of the air humidity and the considerable amount of precipitations that affect the bodies of the peacekeepers most negatively. The level of perception of vital hazards by military pilots proves considerably lower and less significant as compared to that if the military pilots of the Joint Forces Operation. As a result, the adaptation of peacekeepers to the existing conditions of their professional activities lasts 2,4 times longer, though much more successful, as compared to that of the flight crew of the Joint Forces Operations.